Grain Boundary Wetting Phenomena in High Entropy Alloys Containing Nitrides, Carbides, Borides, Silicides, and Hydrogen: A Review - Straumal, Boris; Rabkin, Eugen; Lopez, Gabriel A.; Korneva, Anna; Kuzmin, Alexei; Gornakova, Alena; Straumal, Alexander; Baretzky, Brigitte (MDPI, 2021)
In this review, we analyze the structure of multicomponent alloys without principal components (they are also called high entropy alloys—HEAs), containing not only metals but also hydrogen, nitrogen, carbon, boron, or silicon. In particular, we discuss the phenomenon of grain boundary (GB) wetting by the melt or solid phase. The GB wetting can be complete or incomplete (partial). In the former case, the grains of the matrix are completely separated by the continuous layer of the second phase (solid or liquid). In the latter case of partial GB wetting, the second solid phase forms, between the matrix grains, a chain of (usually lenticular) precipitates or droplets with a non-zero value of the contact angle. To deal with the morphology of GBs, the new GB tie-lines are used, which can be constructed in the two- or multiphase areas of the multidimensional HEAs phase diagrams. The GBs in HEAs in the case of complete or partial wetting can also contain hydrides, nitrides, carbides, borides, or silicides. Thus, GB wetting by the hydrides, nitrides, carbides, borides, or silicides can be used in the so-called grain boundary chemical engineering in order to improve the properties of respective HEAs.--//-- This article is published under the CC BY 4.0 licence.
This review was written during the preparation of M-era.Net full proposal “Grain boundaries in multicomponent alloys without principal component” (A.Ko., A.Ku., G.L., and E.R., application No 9345). We also acknowledge the support of the KIT-Publication Fund of the Karlsruhe Institute of Technology. The Institute of Solid State Physics, University of Latvia, as a center of excellence, has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement no. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; high entropy alloys; grain boundary wetting; precipitation; phase transitions; phase diagrams